Evaluation of Antimicrobial Coatings on Preservation and Shelf Life of Fresh Chicken Breast Fillets Under Cold Storage - Johanna Garavito; Diana Moncayo-Martínez; Diego A. Castellanos (Foods, 2020)
Fresh poultry products such as chicken breast are very convenient for consumption due to their availability and nutritional and sensory characteristics but they have a short shelf life (3–5 days) due to their high water activity and propensity to microbial contamination and spoilage. In this work, the characteristics of edible coatings (EC) prepared from various formulations of guar gum (GG) and isolated soy protein were evaluated. From this evaluation, and due to the guar gum EC being the most suitable, antimicrobial coatings were prepared with different proportions of GG, nisin, and oregano oil to determine its effect on shelf life and change in physicochemical and microbiological properties of chicken breast fillets under refrigerated conditions. Fresh samples were coated with a coating-forming solution based on GG and stored at 4 °C for 16 days. During this time, the change in color, firmness, acidity, pH, growth of microorganisms was determined, and sensory tests of appearance, taste, and odor were performed. GG-coated samples retained color and firmness during storage. Likewise, a decrease in weight loss was achieved in the treated samples, and the sensory attributes were preserved compared to the uncoated samples. The application of the coating considerably delayed the growth of microorganisms, increasing the product shelf life (9 days) compared to the control samples (6 days).